Effect of Itraconazole-Ezetimibe-Miltefosine Ternary Therapy in Murine Visceral Leishmaniasis - Andrade-Neto, Valter V. (Antimicrob Agents Chemother, 2021)
Drug combination therapy is an interesting approach to increase the success of drug repurposing for neglected diseases. Thus, the objective of this work was to evaluate binary and ternary therapies composed of itraconazole, ezetimibe, and miltefosine for the treatment of visceral leishmaniasis. Intracellular Leishmania infantum amastigotes were incubated with the drugs alone or in combination for 72 h. For in vivo experiments, we tested long-course (21 days, once per day) and short-course (5 days, twice per day) treatments for the binary combination of itraconazole and ezetimibe. For the ternary therapy including miltefosine, we adopted the short-course treatment and varied the vehicle. None of the combinations were toxic to macrophages. The binary combination of itraconazole plus ezetimibe and the ternary combination of itraconazole, ezetimibe, and miltefosine had synergistic effects in intracellular amastigotes, for some of the proportions evaluated. Although the in vivo long-course therapy had been more effective than the short-course protocol, it showed hepatic toxicity signs. Ezetimibe has been proven to be able to reduce the parasite burden alone or in combination. Both suspensions of the ternary combination were active, but when the drugs were suspended in the commercial Ora-Plus formulation instead of purified water, the parasite burden was reduced by 98% in the liver and spleen. Altogether, the results demonstrate for the first time the activity of ezetimibe in a viscerotropic species of Leishmania and indicate that ternary treatment composed of miltefosine, itraconazole, and ezetimibe at low doses is a promising therapeutic alternative for the treatment of visceral leishmaniasis.